The Use of Cell Phones to Address Safety Skills for Students With a Moderate ID in Community-Based Settings. (June 2018) - Bassette, Laura A.; Taber-Doughty, Teresa; Gama, Roberto I.; Alberto, Paul; Yakubova, Gulnoza; Cihak, David
The purpose of this study was to examine the impact of a video modeling (VM) intervention in conjunction with a system of least prompts (SLP) to teach safety skills using cell phones to students with a moderate intellectual disability. A multiple-probe design across three participants was used to assess student acquisition in taking and sending a picture of a key identifier (i.e., a sign) during a role-play scenario in which students pretended to be lost in the community. Intervention sessions were conducted at the students' middle school, at their community-based instruction site, and at an unfamiliar community location. All students successfully learned to take and send the picture in the community locations at the mastery criterion and generalized the skills at an unfamiliar community site. Implications of the use of VM to address the integration of technology with safety skill instruction and other areas of future research are discussed.